2004
DOI: 10.1051/0004-6361:20047104
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the non-thermal emission in SN 1006

Abstract: Abstract. SN 1006 is the prototype of shell supernova remnants, in which non-thermal synchrotron emission dominates the X-ray spectrum. The non-thermal emission is due to the cosmic-ray electrons accelerated behind the blast wave. The X-ray synchrotron emission is due to the highest energy electrons, and is thus a tracer of the maximum energy electrons may reach behind a shock. We have put together all XMM-Newton observations to build a full map of SN 1006. The very low brightness above 2 keV in the interior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
160
2
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(185 citation statements)
references
References 34 publications
(59 reference statements)
21
160
2
2
Order By: Relevance
“…Two different integration regions were defined a priori from the XMM-Newton data set (Rothenflug et al 2004): a map of the flux in the 2-4.5 keV energy range (to exclude thermal contamination) was smoothed with the HESS PSF, and regions which contained 80% of the flux were calculated. The two resulting regions, denoted as NE Region and SW Region, are displayed as white contours in Fig.…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Two different integration regions were defined a priori from the XMM-Newton data set (Rothenflug et al 2004): a map of the flux in the 2-4.5 keV energy range (to exclude thermal contamination) was smoothed with the HESS PSF, and regions which contained 80% of the flux were calculated. The two resulting regions, denoted as NE Region and SW Region, are displayed as white contours in Fig.…”
Section: Morphologymentioning
confidence: 99%
“…The HESS profile is compatible with a superposition of two Gaussian emission regions almost at 180 • from each other, respectively The white cross indicates the geometrical centre of the SNR obtained from XMM data as explained in the text and the dashed circles correspond to R ± dR as derived from the fit. The white star shows the centre of the circle encompassing the whole X-ray emission as derived by Rothenflug et al (2004) and the white triangle the centre derived by Cassam-Chenaï et al (2008) from Hα data. The white contours correspond to a constant X-ray intensity as derived from the XMM-Newton flux map and smoothed to the HESS point spread function, enclosing respectively 80%, 60%, 40% and 20% of the X-ray emission.…”
Section: Morphologymentioning
confidence: 99%
“…This velocity is in a good agreement with analogous velocity measurements by Smith et al (1991) which give v = 2200−3500 km s −1 . At this distance the SNR apparent size 15 (Rothenflug et al 2004) translates into a shock radius equal to r shock = 9.6 pc. A value for the ambient gas density equal to n = 0.15−0.25 cm −3 (in the north-western region) has been obtained by Acero et al (2007) from XMM X-ray observations.…”
Section: Application Of the Model To The Supernova Remnant Sn 1006mentioning
confidence: 97%
“…Using XMM-Newton, Rothenflug et al (2004) have shown very strong azimuthal variations that cannot be explained by variations of the magnetic compression alone. The maximum energy of the accelerated particles is higher at the bright synchrotron limbs than elsewhere.…”
Section: Electron Accelerationmentioning
confidence: 99%